A model for human skin impedance during surface functional neuromuscular stimulation - REILLY, RICHARD (IEEE, 1999)
A new mathematical model for the bulk electrical impedance of human skin is presented. In particular this model describes the impedance of skin during surface functional neuromuscular stimulation (FNS) with square stimulation pulses. Experimental data are presented that illustrate the nonlinear dynamic properties of human skin during current and voltage controlled stimulation. Model predictions are compared to experimental data, measured under both constant voltage and constant current transcutaneous stimulation. It is found that this model captures a variety of nonlinear time-varying effects observed in the skin impedance when stimulating with either protocol. This model may be used as part of large neuromusculoskeletal models or in the more accurate modeling of transcutaneous FNS, which is currently the most common clinical implementation of FNS.
PUBLISHED
Keywords: impedance; modeling; neuromuscular stimulation